(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines Sylvia Plath’s intricate use of mythology and archetypes in her poetry and prose, revealing how these elements serve as vehicles for exploring themes of identity, femininity, and psychological struggle. By engaging with classical myths and Jungian archetypes, Plath reinterprets traditional narratives, transforming figures such as Persephone, Electra, and Medusa into symbols of female experience and empowerment. This analysis focuses on how Plath’s invocation of these mythological and archetypal figures allows her to articulate the complexities of womanhood, particularly the tensions between societal expectations and personal identity.